Eerdmans dictionary of the Bible = Dictionary of the Bible - Freedman, David Noel 1922-2008 (Eerdmans, 2009)
"This outstanding source is the place to find definitions, personal names and their derivation, places, and concepts from the Bible. Six hundred leading scholars from a wide spectrum of theological perspectives have come together to provide almost 5,000 articles that reflect current biblical scholarship, archaeological discoveries, trends, and issues. A must for every library."--"Outstanding Reference Sources," American Libraries, May 2002